Financial Performance against Sukuk Ratings in the Islamic Finance Sector - Sufyati HS (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research examined the evaluations of Sukuk. Sukuk refers to the Fatwa of the National Sharia Council; sharia bonds or Sukuk are long-term sharia-compliant securities issued by Issuers to Sharia Bondholders. Additionally, the Sukuk rating serves as a barometer for potential investors to assess if the Sukuk's performance is positive or negative. The objective of this study is to examine the financial performance's impact. Sukuk Ratings in the Islamic financial industry, namely Islamic Commercial Banks, as a sample based on purposive sampling with particular criteria for credit risk, return on assets (ROA), and firm size. The data in this study is derived from secondary sources and analyzed using multiple linear regression techniques. According to the findings of this study, the ROA variable has a substantial influence on the Sukuk rating. By contrast, the factors Current Ratio and Firm Size have no discernible effect on the Sukuk rating. This is demonstrated by the t-test, which indicates that the ROA variable has a significant value, but the Current Ratio and Firm Size variables do not.